Study of the first outbreak of bluetonge disease in sheep in Greece - ΜΑΣΤΡΟΠΑΝΝΗ, Μ.; ΑΞΙΩΤΗ, Ι.; ΣΤΟΦΟΡΟΣ, ΕΥΘ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Epidemiological data and the virus isolation concerning the first outbreak of bluetongue, in autumn 1979 in sheep in Lesvos Island are reported. Sixty eight flocks with a total number of 5950 sheep were infected causing a morbidity rate from 10 to 90% and 28% mortality of the diseased sheep. The distance of the place, where the first flock was infected, from Turkish coast is about six miles. The caracteristic of the summer of that year was the prevalance of the strong north-east winds (seasonal winds) and the high temperatures in autumn. The aerogenic route may be the possible route of transmission (cullicoides) , since many years have not been imported runimants in the Island from Turkey ofTicialy. The virus of BT was isolated in chicken embryonated eggs following i/v inoculation. Neutralising antibodies against BTV type 4 were detected in the sera of convalescent sheep. Also, in the Onderstepoort Institute was isolated and identified the virus of BT as type 4 from pathological material we sent.